Eliminating Abortion from Criminal Law in Colombia: A Just Cause - Ana Cristina González-Vélez; Carolina Melo-Arévalo; Juliana Martínez-Londoño (Harvard FXB Center for Health and Human Rights, 2019)
The two main legal models governing abortion provision, indications for abortion and time limits on the number of weeks of pregnancy, both limit recognition of women's reproductive autonomy. Each model restricts the circumstances under which women can access abortion. Yet, in most of the world these have been the main political goals for the feminist movement in the fight to make abortion legal and safe. Other strategies have also been incorporated into these goals. But in each case, abortion remains a crime, causing pervasive and profound damage for the providers and for women, and maintaining abortion as a part of an exceptionality regime suspended in its own illegality. This article discusses such limitations. It then focuses on Colombia and the experiences of feminist collective La Mesa por la Vida y la Salud de las Mujeres, which is campaigning to have abortion removed from the criminal law. In particular, this article examines a double standard in Colombian law: while abortion has been declared a fundamental right, it remains a crime in the penal code.